Fidel Castro and the Sierra Maestra. A deliberately chosen theater of operations? - Yves Lacoste (Geografares, 2022)
Translation of the article “Fidel Castro et la Sierra Maestra. Un théâtre d’opérations volontairement choisi?”, by Yves Lacoste, published in Hérodote magazine in its 5th issue, concerning the 1st quarter of 1977, p. 7-33.